SIMULATION FOR IMPROVEMENT OF DC MOTOR CONTROLLERS’ RESPONSE WITH APPLICATION TO A MOBILE ROBOT - Hasan, Shameem; Sarowar, Golam (Institute of Advanced Engineering and Science, 2020)
In this study, different precise and appropriate control mechanisms for speed and steering control of a robot with mobile movement that use a Direct Current motor, have been simulated for improved controllers? response. Proportional-Integral-Derivative (PID), Lead-Lag compensator, and Fuzzy Logic Controller (FLC) are designed as well as simulated to provide command over the angular speed of a Direct Current motor mounted in the robot. The response of the Direct Current motor for every controller is observed and compared among each other for a sinusoidal and a step input which indicate speed as well as position respectively of mobile robot. The performance analysis indicates that the Lead-Lag compensator and PID controller can be considered effective for the task assigned for steering the wheel and Fuzzy Logic Controller (FLC) is efficient for wheel speed controlling. Considering the overall improved performance of the mobile robot in terms of precision of speed control as well as steering capability, it seems reasonable to conclude that the proposed design criteria were effective and satisfactory.